2018
DOI: 10.1186/s12884-018-2119-0
|View full text |Cite
|
Sign up to set email alerts
|

Continuous support during labour in childbirth: a Cross-Sectional study in a university teaching hospital in Shanghai, China

Abstract: BackgroundFear or anxiety could result in adverse consequences on the course of labour. To date, family members are still not permitted in the delivery rooms in the majority of hospitals in China, and continuous support from hospital professional staff is also limited. This study aimed to evaluate the benefits of continuous support by family members and hospital professional staff during labour in China.MethodsIn this Cross-Sectional study, 362 primiparous pregnancies who self-requested to receive continuous o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 27 publications
0
14
1
7
Order By: Relevance
“…In the metaanalysis of randomized controlled studies by Hodnett et al (10) was found that continuous labor support reduced interventions in labor process, similar to our study. However, Sandall et al (18) and Man Wang et al (19), unlike these results, they did not detect any change in the intervention rates in the group they gave birth support.…”
Section: Discussionmentioning
confidence: 68%
“…In the metaanalysis of randomized controlled studies by Hodnett et al (10) was found that continuous labor support reduced interventions in labor process, similar to our study. However, Sandall et al (18) and Man Wang et al (19), unlike these results, they did not detect any change in the intervention rates in the group they gave birth support.…”
Section: Discussionmentioning
confidence: 68%
“…Wang (15) showed that the cesarean rate was significantly lower in women with supportive care compared to women with routine maternal care in the hospital (3.3% versus 24%), the duration of labor in the group with delivery care was significantly lower compared with that of the group with routine hospitalization (median: 1.5 h versus 3.05 h, p <0.0001). these results were much lower than those found in the present study (median: 6.7 h versus 13.4 h) and those reported by Borhen, that of 13 studies taken into account for the duration of labor, 6 had significantly lower means in the support group and an average of 6.97 h for the groups with support and an average of 8.46 h for groups without support (8).…”
Section: Discussionmentioning
confidence: 99%
“…Different strategies have been devised to try to reduce cesarean deliveries, as continuous intrapartum support, which has been associated with better patient satisfaction and a statistically significant reduction in the cesarean delivery rate (7), (8), (9), (10), (11), in previous studies this support has been provided by a doula and the husband (12), midwives (13), female relative (14), relatives and professional staff (15). Bohren in his systematic review of the Cochrane database, indicates that it is not clear how to provide effective support in labor, since there are questions about the impact of the type of provider of labor support, about the impact under a variety of environmental conditions, about the moment of measurement of the effects (early vs active labor), also on the relative impact of the different models of labor support, as the model of support only during the intrapartum period or the model of support during the antenatal, intrapartum and postpartum periods (8).…”
mentioning
confidence: 99%
“…(39) kadınların desteklendiği doğumlarda mekonyum aspirasyon ve doğum asfiksisinde önemli azalma olduğunu bildirirken, Wang ve ark. (40) doğumda sürekli desteklenen kadınların acil sezaryen oranlarının ciddi oranda düştüğünü bildirmektedir. Greiner ve ark.…”
Section: Discussionunclassified